Impacts of two years of autumn cover crops in northwestern Washington on winter annual weed populations. Issue 2 (21st March 2023) - Seefeldt, Steven S.; Una, Toby M.; McMoran, Don; Maupin, Brian; Myhre, Elizabeth; Griffin-LaHue, Deirdre
Abstract: Cover cropping is a suggested soil conservation practice widely investigated in cropping systems. Cover crops suppress weeds and often are part of an integrated weed management plan that could lead to reduced herbicide use and possibly reduce the weed seedbank. Winter brassica cover crops are popular in the eastern Washington potato ( Solanum tuberosum L.) production region, but in western Washington, the production of brassica seed crops presents disease issues along with the risk of cross-pollination, which limits the use of brassica cover crops. Research for this article was conducted in two trials from 2018 to 2020 and 2019 to 2021in Mount Vernon, Washington, to identify winter cover crops compatible with regional restrictions and climatic challenges in western Washington cropping systems. Treatments including a no-cover control, eight single species (including brassicas, grasses, and legumes), and a grass–legume mixture were investigated. Cover crop and weed biomass production were measured, and percent ground cover for cover crops and weeds by species was estimated. Cover crop biomass and weed suppression varied by year due to variable environments, but annual ryegrass ( Lolium multiflorum Lam.) and the mixture were most consistent in producing large amounts of biomass and reducing weed biomass and cover in all years. The variability of percent weed cover response to environment was ameliorated when weed cover was normalized within each year's control.